Ultrasound imaging versus palpation method for diagnostic lumbar puncture in neonates and infants: a systematic review and meta-analysis - Abiola Olowoyeye; Opeyemi Fadahunsi; Jerome Okudo; Oluwakare Opaneye; Charles Okwundu (BMJ Publishing Group, 2019)
Importance Lumbar puncture (LP) failure rates vary and can be as high as 65%. Ultrasound guidance could increase the success of performing LP.Objective To summarise the evidence on the use of ultrasound guidance versus palpation method for LP.Data sources We searched computerised databases and published indexes, registries and references identified from bibliographies of pertinent articles without any language restrictions to find studies that compared ultrasound guidance to palpation method for performing an LP.Study selection Studies were included if they were randomised or quasirandomised trials in neonates and infants that compared ultrasound guidance with palpation method for performing an LP.Data extraction and synthesis Standardised data collection tool was used for data extraction, and two reviewers independently assessed the quality of the studiesMain outcome(s) and measure(s) The primary outcome was the risk of LP failure, while the risk of traumatic tap, needle redirections/reinsertions and procedure durations were secondary outcomesResults Data from four studies and 308 participants is included in the analysis. Ultrasound imaging reduced the risk of LP failure, risk ratio of 0.58 (95% CI 0.15 to 2.28), but it was not statistically significant (p=0.44). Ultrasound imaging significantly reduced the risk of a traumatic tap risk ratio of 0.33 (95% CI 0.13 to 0.82) and p=0.02. The included studies had low to moderate quality; the studies differed based on mean age and with variability on outcome definition.Conclusions and relevance This meta-analysis suggests that ultrasound imaging has no effect in increasing lumbar success but is beneficial in reducing the risk of traumatic taps in neonates and infants.Trial registration number CRD42017055800.